2022
DOI: 10.3390/ijms23052577
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids: An Insight into the Pathogenesis of Neurodegenerative Diseases and Therapeutic Potential

Abstract: One of the most common lipids in the human body is palmitic acid (PA), a saturated fatty acid with essential functions in brain cells. PA is used by cells as an energy source, besides being a precursor of signaling molecules and protein tilting across the membrane. Although PA plays physiological functions in the brain, its excessive accumulation leads to detrimental effects on brain cells, causing lipotoxicity. This mechanism involves the activation of toll-like receptors (TLR) and nuclear factor kappa-light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 245 publications
(379 reference statements)
1
24
0
Order By: Relevance
“…A significant increase in unsaturated lipid content in the 10 mg/kg TQ group compared to the control group was observed in the present study. The study showed that unsaturated fatty acids decrease inflammatory responses, saturated fatty acid-induced cytotoxicity, and ROS production in various models of brain damage and neurodegenerative diseases (29). Moreover, total antioxidant capacity of cerebellum tissues of rats treated with 10 mg/kg TQ was significantly increased when compared with the control according to the present study's results.…”
Section: Discussionsupporting
confidence: 71%
“…A significant increase in unsaturated lipid content in the 10 mg/kg TQ group compared to the control group was observed in the present study. The study showed that unsaturated fatty acids decrease inflammatory responses, saturated fatty acid-induced cytotoxicity, and ROS production in various models of brain damage and neurodegenerative diseases (29). Moreover, total antioxidant capacity of cerebellum tissues of rats treated with 10 mg/kg TQ was significantly increased when compared with the control according to the present study's results.…”
Section: Discussionsupporting
confidence: 71%
“…Disorder of lipid metabolism, especially when the palmitic acid (PA) accumulates, would cause lipid-overload lipotoxicity and inhibit the autophagic flux in neurons, which is the whole autophagic process from the synthesis of the autophagosomes to their lysosomal fusion and degradation (Fang et al, 2020 ; Hernández-Cáceres et al, 2020 ; Chung, 2021 ; Vesga-Jiménez et al, 2022 ). PA induces APP palmitoylation and enhances Aβ accumulation via proteolytic processing of APP by multiple enzymes, such as BACE1, β-secretase, and γ-secretase (Kim et al, 2017 ; Zareba-Kozioł et al, 2018 ).…”
Section: Dietary Therapy Hypothesismentioning
confidence: 99%
“…And in Sirt3 -silenced mouse brain-derived endothelial cells, the neuro-inflammatory response was exacerbated (Tyagi et al, 2021 ). Many researchers proposed the use of unsaturated fatty acids (UFA), such as oleic acid (OA) or linoleic acid (LA), as a potential therapeutic approach against AD, because that these UFA could counteract PA's detrimental effects on cells (Piomelli, 2013 ; Vesga-Jiménez et al, 2022 ). For example, oleic acid ingestion stimulates oleoylethanolamide mobilization into the mucosal cells of the gut, which triggers a peroxisome proliferator-activated receptor (PPAR)-mediated signals that travel through the afferent vagus nerve to the hypothalamus, augmenting satiety and showing beneficial effects to the nervous system (Piomelli, 2013 ).…”
Section: Dietary Therapy Hypothesismentioning
confidence: 99%
“…PA is the most common SFA, accounting for 20–30% of the total fatty acids in the human body. It has been considered detrimental to the health because it causes lipotoxicity [ 104 ], although its negative effects may be related to an imbalance of dietary PA/PUFAs [ 105 ]. PA appears to inhibit the proliferation of mouse-derived NPCs and favor astrogliogenesis, an effect associated with the activation of Stat3 (a transcription factor that promotes astrogliogenesis) [ 106 ].…”
Section: Fatty Acids and Neurogenesismentioning
confidence: 99%